Passive sonar with cylindrical array - Marszal, J.; Leśniak, W.; Salamon, R.; Jedel, A.; Zachariasz, K. (Archives of Acoustics, 2006)
The article presents a method of using active sonar with cylindrical array for passive monitoringof underwater sound sources. It is demonstrated that detecting a sound source anddetermining its bearings may be carried out with no changes in the construction of the receiver.Changing signal processing algorithms in the beamformer is all that is required. It isalso demonstrated that in order to increase the accuracy of determining bearing it is possibleto use high-resolution methods of spatial spectrum estimation. The methods are effectivefor angles of wave incidence contained in sonar’s beam width. Inaccuracies for larger anglesresult from uneven sampling of acoustic field distribution.